Socioeconomic Status Influences Functional Severity of Untreated Cerebral Palsy in Nepal: A Prospective Analysis and Systematic Review. Issue 1 (January 2019) - LeBrun, Drake G.; Banskota, Bibek; Banskota, Ashok K.; Rajbhandari, Tarun; Baldwin, Keith D.; Spiegel, David A.
Abstract: Background: Cerebral palsy (CP) comprises a heterogeneous group of disorders whose clinical manifestations and epidemiologic characteristics vary across socioeconomic and geographic contexts. The functional severity of untreated CP in low-income countries has been insufficiently studied; a better understanding of how these children present for care in resource-constrained environments is important because it will better characterize the natural history of CP, guide clinical decision-making, and aid in the prognostication of children with untreated CP. Questions/purposes: The purposes of this study were (1) to determine the etiologies, motor subtypes, topographic distributions, and functional classifications of a large cohort of Nepali children with untreated CP presenting to a large pediatric rehabilitation center in Nepal; and (2) to compare the Gross Motor Function Classification System (GMFCS), the Manual Ability Classification System (MACS), and the Communication Function Classification System (CFCS) scores of a subset of patients with spastic CP in the Nepali cohort with control subjects from high-income countries. Methods: A cross-sectional study was conducted at the Hospital and Rehabilitation Centre for Disabled Children in Nepal. Two hundred six consecutive Nepali children (76 girls; median age 4.0 years [interquartile range IQR, 2.5–9.0 years]) were evaluated to determine the demographic, clinical, and functional characteristics of a cohort of Nepali children with untreated CP. A systematic review of the Medline and Cochrane databases was then performed to obtain reference classification scores from high-income countries. Cross-sectional, noninterventional studies reporting at least one functional classification system with a sample size of at least 50 participants were included. Only studies of patients with spastic CP were included to allow for compatible comparisons with a subset of our study sample with spastic CP. A random-effects analysis was used to pool functional scores from participants in the included studies. Among the 206 children in our sample, 102 had spastic CP (35 girls; median age 5.5 years [IQR, 3.5–9.0 years]). Functional scores from these children were compared with pooled scores obtained from the systematic review by assessing the proportions of children in each sample with GMFCS, MACS, and CFCS score categories of I or II versus III to V. Results: Children with spastic hemiplegia from high-income countries were more likely to have a GMFCS score of I or II (96% [95% confidence interval CI, 92%-99%] versus 78% [95% CI, 62%-89%]) and a MACS score of I or II (83% [95% CI, 77%-88%] versus 50% [95% CI, 32%-68%]) relative to those from Nepal, but they were less likely to have a CFCS score of I or II (67% [95% CI, 51%-80%] versus 97% [95% CI, 87%-99%]). No differences were seen in children with spastic diplegia or quadriplegia. Conclusions: Children in Nepal with hemiplegic CP have greater functional disability despite less motor impairment compared with children from high-income settings. Targeted interventions to maintain functional status in Nepali children with CP may reduce this disparity. Additional studies demonstrating the association between socioeconomic status and the prognosis of CP in resource-limited populations are needed. Level of Evidence: Level II, prognostic study.